The Effects of Square and Circular Die-Orifices on the Performance of Combined Extrusion-Forging Process - Sezek, S.; Misirli, C.; Aksakal, B.; Can, Y. (Springer, 2012)
The upper bound (UBM) and finite element methods (FEM) both coupled with experiments have been conducted to analyze forming performance, load prediction, and pressure analyses in a combined extrusion-forging process using square and circular die orifices. The forming load was predicted by the UBM and the pressure distribution was analyzed by FEM and the performance of both the methods was compared to each other. The required extrusion forging force for square die orifice was found to be higher than in the circular die orifice. The highest pressures occurred on the edges of the square and circular orifices and the pressures increased with increasing friction and deformation. Although extrusion force predictions were found to be slightly higher in UBM than FEM, they were in good agreement with experimental results. The present analyses showed that UBM can be used in rapid prediction of required extrusion-forging loads and material flow, and FEM is more suitable to use in pressure distribution analysis for production of square and cylindrical parts.
Keywords: extrusion; FEM; forging; forming loads; upper bound